Food Security and the Process of Sustainable Development between Kazakhstan and China (International relations and international law Journal, 2025)
In recent years, agricultural cooperation between Kazakhstan and China has become a strategically important area for the economic, political, and environmental development of both countries. Amid climate change, food price volatility, the emergence of new conflict hotspots worldwide, and global resource shortages, ensuring food security is a key prerequisite for long-term sustainable development for both states.Kazakhstan’s vast agricultural lands and natural potential, combined with China’s growing demand for agricultural products, are opening up new opportunities for bilateral cooperation. The increased volume of agricultural trade and the rising number of projects in processing and logistics sectors in recent years highlight the importance of this partnership. However, several issues still require attention, including transparency of land-use mechanisms, environmental safety, protection of national interests, and harmonization of regulatory systems.This study provides a comprehensive analysis of Kazakhstan–China agricultural cooperation in the context of food security and sustainable development. Through literature review, quantitative and qualitative analysis, and political assessment, it examines trade dynamics and the impact of joint projects between 2020 and 2023. The analysis reveals the opportunities and limitations of bilateral interaction and offers recommendations to support strategic decision-making.Overall findings emphasize Kazakhstan’s growing role in the global agricultural market and the strategic importance of its partnership with China. At the same time, the gradual increase in dependence on China requires a deeper understanding of the dynamics of bilateral relations.Keywords: food security, sustainable development, Kazakhstan, China, agricultural relations.